ನಿರಂತರ - Mallikarjun, B.; Yadurajan, S.S. (My University, 2000)
The present monograph Nirantara is an attempt to transfer technology of teaching Kannada Efficiently in the secondary schools of Karnataka.
Nirantara Teaching Kannada in Secondary Schools
Keywords: Kannada